The Effect of Quality of Nursing Service to Patients Satisfaction Level in Hospitality of Partial Reliance and Total Hospital of Sundari General Hospital - Mhd. Fadli; Arifah Devi fitriani; Asriwati Amirah (Journal La Medihealtico, 2020)
The quality of health services is one of the basic needs that everyone needs. The low quality of nursing services is in line with the low level of patient satisfaction so it is necessary to improve the quality of nursing services in order to increase patient satisfaction. This study aims to determine the effect of the quality of nursing services of the level satisfaction of partial and total dependence inpatient midwifery in Sundari General Hospital in 2020. The type of research is a descriptive-analytic survey with cross-sectional research. The population in the study were all partial and total dependence inpatient midwifery RSU Sundari Medan and the sample of 72 people. Methods of data analysis by means of univariate analysis, bivariate analysis, and multivariate analysis with multiple logistic regression tests. The results of the study statistically showed safety, hygiene of body care, comfort, and anxiety affect the level satisfaction of partial and total dependence inpatient midwifery (p <0.05). The results of multiple logistic regression tests found variables that the most influence patient satisfaction is safety and comfort. Safety is the most dominant factor in influencing patient satisfaction. It can be concluded that there is an effect of safety, hygiene of body care, comfort, and anxiety of the level satisfaction of partial and total dependence inpatient midwifery. Suggested by the hospital, it is necessary to increased training in safety during postnatal care through providing actions to patients so that safety measures provide satisfaction. Training needs to be provided to provide relaxation techniques that are appropriate for nursing instructions so feel comfortable.